ZnO-Doped gC3N4Nanocapsules for Enhancing the Performance of Electroless NiP Coating─Mechanical, Corrosion Protection, and Antibacterial Properties3N4Nanocapsules for Enhancing the Performance of Electroless NiP Coating─Mechanical, Corrosion Protection, and Antibacterial Properties - Fatma Nabhan (16324958) (2023)
A carbon nitride (C3N4) nanomaterial has superior mechanical, thermal, and tribological properties, which make them attractive for various applications, including corrosion-resistant coatings. In this research, newly synthesized C3N4 nanocapsules with different concentrations (0.5, 1.0, and 2.0 wt %) of ZnO as a dopant were incorporated into the NiP coating using an electroless deposition technique. The nanocomposite coatings either ZnO-doped (NiP-C3N4/ZnO) or undoped (NiP-C3N4) were heat-treated at 400 °C for 1 h. The as-plated and heat-treated (HT) nanocomposite coatings were characterized by their morphology, phases, roughness, wettability, hardness, corrosion protection, and antibacterial properties. The results indicated that the microhardness of as-plated and heat-treated nanocomposite coatings was significantly improved after the incorporation of 0.5 wt % ZnO-doped C3N4 nanocapsules. The outcomes of electrochemical studies revealed that the corrosion resistance of the HT coatings is higher than the corresponding as-plated ones. The highest corrosion resistance is achieved on the heat-treated NiP-C3N4/1.0 wt % ZnO coatings. Although the presence of ZnO in the C3N4 nanocapsules increased its surface area and porosity, the C3N4/ZnO nanocapsules prevented localized corrosion by filling the microdefects and pores of the NiP matrix. Furthermore, the colony-counting method used to evaluate the antibacterial behavior of the different coatings demonstrated superior antibacterial properties, namely, after heat treatment. Therefore, the novel perspective C3N4/ZnO nanocapsules can be utilized as a reinforcement nanomaterial in improving the mechanical and anticorrosion performance of NiP coatings in chloride media, together with providing superior antibacterial properties. Other Information Published in: ACS Omega License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1021/acsomega.2c07288